Non-text ticket machine interface design using linguistic typology / Carolyne Norlie Manggi@Khairulisa Norlie Manggi - Norlie Manggi, Carolyne@Khairulisa (2008)
Ticket machine has been defined as public technology devices. Despite of its convenience, there are groups of people, known as functional illiterate cannot fully utilize the use of this technology. It's due to their disability to read text and poor presentation of ticket machine interface design, which is using fully text-based. Thus, non-text interface design using Linguistic Typology could possibly eradicate this problem. This project studied and analyzed the features of Linguistic Typology, determined and design non-text elements that can represent ticket machine transaction process using linguistic typology and finally develop the simulation of non-text ticket machine interface design using Linguistic Typology. The arrangement of the icons are followed the Verb-Subject-Object and Verb-Subject order based on Linguistic Typology. This simulation guides the users to make the transaction process in sequential steps. Linguistic typology is suitable for ticket machine transaction design because people can make a simple phrase based on the icons' arrangement that they have been chosen. Thus indirectly improve the learnability on ticket machine interface design. The users are guided properly using non-texts element such as sounds, animations and pictures.